Enhancement of biodegradable polymer properties by physical and chemical revisited method - M. Esfahan, Zahra; Nekoui, Soheil; Ismail, Mohd Halim Shah; Pourzolfaghar, Hamed (World Academy of Research and Publication, 2014)
Recently, interested in compound production has moved towards using natural polymers as strengthening due to the environmental advantages. The use of Bio-degradable matrices is worth considering since this will result in fully biodegradable compound. In to evaluate the most appropriate array plastic, one has to know the property of available plastics. Since information tends to be dispersed over several sources and are very rare in comparison to the traditional polymer materials, it is the goal of this article to provide an overview of the most relevant property of the range are biodegradable polymeric. A review like the one shown here can provide a helpful guide to establish the best balance between the comparing properties requirements.